Bioinspired Peptoid Nanotubes for Targeted Tumor Cell Imaging and Chemo‐Photodynamic Therapy. Issue 43 (30th August 2019) - Luo, Yanan; Song, Yang; Wang, Mingming; Jian, Tengyue; Ding, Shichao; Mu, Peng; Liao, Zhihao; Shi, Qiurong; Cai, Xiaoli; Jin, Haibao; Du, Dan; Dong, Wen‐Ji; et al.
Abstract: Substantial progress has been made in applying nanotubes in biomedical applications such as bioimaging and drug delivery due to their unique architecture, characterized by very large internal surface areas and high aspect ratios. However, the biomedical applications of organic nanotubes, especially for those assembled from sequence‐defined molecules, are very uncommon. In this paper, the synthesis of two new peptoid nanotubes (PepTs1 and PepTs2) is reported by using sequence‐defined and ligand‐tagged peptoids as building blocks. These nanotubes are highly robust due to sharing a similar structure to those of nontagged ones, and offer great potential to hold guest molecules for biomedical applications. The findings indicate that peptoid nanotubes loaded with doxorubicin drugs are promising candidates for targeted tumor cell imaging and chemo‐photodynamic therapy. Abstract : A new class of uniform 1D peptoid nanotubes with high stability is developed by the assembly of ligand‐tagged Nbpm6 Nce6 peptoid oligomers. These nanotubes exhibit a high loading efficiency to doxorubicin. Additionally, the photosensitizer‐conjugated nanotubes induce the generation of singlet oxygen and the activation of cell apoptosis. A chemo‐photodynamic therapy combined killing effect is achieved by the drug‐loaded functional nanotubes.